The effect of a rehabilitation physical program using compound exercises to reduce the degree of pain and improve some physical abilities in a torn posterior muscle (hamstring) injury for second-degree football players - Ahmed Allawi (College of Physical Education and Sport Sciences, 2023)
The posterior muscle tear injury is one of the most common football injuries in the world and in Iraq in particular, as failure to study it and develop appropriate physical and rehabilitation programs for it based on solid scientific foundations will lead to the injury recurring again, and this leads the player to leave the field and be deprived of playing in the field. In the future, she must recover well. Since football requires changing direction and relying on one leg in some cases of play, jumping and speed, as well as turning, stopping directly, and many other movements that occur during matches and training, these movements cause effort on the muscle itself, the tendon and the ligament. Most players and coaches pay attention to training the quadriceps and do not pay attention to training the back muscle, and this leads to an imbalance between the front and back muscles, which leads to injury and its recurrence. The primary goal of the research is to identify the effect of combined physical and rehabilitative exercises for a ruptured posterior muscle in football players. The study was conducted on a sample of players with a ruptured posterior muscle, whose ages ranged from (17 to 23) years, and their number reached 6 patients. The researcher used the experimental method to measure the pretest for one group. The researcher used the statistical method SPSS. The researcher concluded that the physical exercises that the researcher developed in the physical and rehabilitation curriculum had a significant impact on developing the physical research variables. The researcher also concluded that the training methods he put into the program had a positive impact in improving the research results, such as the static and dynamic muscle training method.